Body fat distribution and insulin resistance among Korean middle-aged women: a Korean National Health and Nutrition Examination Survey - Sae Mi Lee; Ki-Jin Ryu; Serhim Son; Yeon Ju Lee; Hyuntae Park; Tak Kim (Korean Society of Obstetrics and Gynecology, 2022)
Objective To evaluate menopause-related changes in body fat distribution and their relationship with insulin resistance in middle-aged Korean women. Methods We analyzed women aged 40-60 years using data from the National Health and Nutrition Examination Survey conducted from 2008 to 2011. Body fat was measured using dual-energy X-ray absorptiometry. Insulin resistance was assessed using the homeostasis model assessment of insulin resistance (HOMA-IR). Results Among 3,468 participants, menopausal women (n=1,489) had a higher body mass index (BMI) and higher trunk, arm, and head fat percentages than premenopausal women (n=1,979). However, no significant difference was found in the leg fat percentage according to menopausal status. Multivariable regression analysis for HOMA-IR showed that trunk fat percentage, BMI, and waist circumference positively correlated with insulin resistance and leg fat percentage negatively correlated after adjusting for several confounding factors, whereas menopausal status was not associated with HOMA-IR. Conclusion Middle-aged women not only have different body weights and BMI but also have different body fat distributions according to menopausal status. Each fat percentage change in the trunk and leg is differently associated with metabolic health, particularly insulin resistance. To evaluate the metabolic health of middle-aged women, BMI is generally noted; however, body fat distribution, which can be easily assessed using dual-energy X-ray absorptiometry, should also be considered.